1976
DOI: 10.1139/b76-142
|View full text |Cite
|
Sign up to set email alerts
|

Pure culture synthesis of bearberry mycorrhizae

Abstract: Synthesis of bearberry (Arctostaphylos uva-ursi) ectendomycorrhizae in pure culture by Hebeloma crustuliniforme, Laccaria laccata, Lactarius sanguifluus, Pisolithus tinctorius, Poria terrestris vars. cyaneus and subluteus, Rhizopogon vinicolor, and Thelophora terrestris is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1977
1977
2007
2007

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…L. deterrimus for example, is exclusively associated with Picea, whereas S. plorans occurs exclusively with five-needled Pinus species, in Europe P. cembra. These observations agree with in vitro studies by Zak (1976) and Molina and Trappe (1982) who observed ''specific fungi'' on the roots of Arctostaphylos spp., too. Two factors are probably responsible for this ''nonselectivity'': (i) A. uva-ursi is a plant with a generally very reduced specificity for mycobionts, thus allowing a mycorrhization with fungal partners which are highly specialized to another plant.…”
Section: A Uva-ursi Is a Non-selective Host With Potential Inoculum supporting
confidence: 92%
See 1 more Smart Citation
“…L. deterrimus for example, is exclusively associated with Picea, whereas S. plorans occurs exclusively with five-needled Pinus species, in Europe P. cembra. These observations agree with in vitro studies by Zak (1976) and Molina and Trappe (1982) who observed ''specific fungi'' on the roots of Arctostaphylos spp., too. Two factors are probably responsible for this ''nonselectivity'': (i) A. uva-ursi is a plant with a generally very reduced specificity for mycobionts, thus allowing a mycorrhization with fungal partners which are highly specialized to another plant.…”
Section: A Uva-ursi Is a Non-selective Host With Potential Inoculum supporting
confidence: 92%
“…Zak (1976) assumed that most fungal partners of arbutoid mycorrhizae are www.elsevier.com/locate/foreco Forest Ecology and Management 250 (2007) [167][168][169][170][171][172][173][174][175] basidiomycetes, being very likely the same species that form ECM of forest trees. This hypothesis was corroborated by Molina and Trappe (1982) who found that in vitro 25 out of 28 cultures of ectomycorrhizal fungi isolated from diverse host-and habitat associations formed arbutoid mycorrhizae with Arbutus menziesii Pursh and A. uva-ursi.…”
Section: Introductionmentioning
confidence: 99%
“…Rhizopogon occidentalis mycorrhizas were cream to buff, occasionally slightly pink stained, and usually lacked rhizomorphs. Rhizopogon vinicolor mycorrhizas were cream white, becoming pale brown to dark brown with age; the oldest mycorrhizas became loosely enveloped by mycelium and threadlike rhizomorphs as noted by Zak (1976b).…”
Section: Resultsmentioning
confidence: 87%
“…For example, Pearson and Read (1975a) showed that endophytes from each of the genera Calluna, Erica, Vaccinium, and Rhododendron would infect the other three genera, regardless of the genus of origin. Little is known about relations in arbutoid mycorrhizae, but nonspecificity may characterize these also, for Zak (1976) reported that seven different genera of basidiomycetes could form mycorrhizae with Arctostaphylos in the laboratory.…”
Section: Host-fungus Specificitymentioning
confidence: 99%